Breakthrough therapy cancer drugs and indications with FDA approval: development time, innovation, trials, clinical benefit, epidemiology, and price - Michaeli, Daniel; Michaeli, Christoph T. (Journal of the National Comprehensive Cancer Network, 2024)
Background: The breakthrough therapy designation (BTD) facilitates the development of drugs with a large preliminary benefit in treating serious or life-threatening diseases. This study analyzes the FDA approval, trials, benefits, unmet needs, and pricing of breakthrough and nonbreakthrough therapy cancer drugs and indications. Patients and Methods: We analyzed 355 cancer indications with FDA approval (2012-2022). Breakthrough and nonbreakthrough indications were compared regarding their FDA approval, innovativeness, clinical trials, epidemiology, and price. Data were extracted from FDA labels, the Global Burden of Disease study, and the Centers for Medicare & Medicaid Services. Hazard ratios (HRs) for overall survival (OS), progression-free survival (PFS), and relative risk (RR) of tumor response were meta-analyzed across randomized controlled trials. Objective response rates (ORRs) were meta-analyzed for single-arm trials. Results: We identified 137 breakthrough and 218 nonbreakthrough cancer indications. The median clinical development time was 3.2 years shorter for breakthrough drugs than for nonbreakthrough drugs (5.6 vs 8.8 years; P=.002). The BTD was more frequently granted to biomarker-directed indications (46% vs 34%; P=.025) supported by smaller trials (median, 149 vs 326 patients; P<.001) of single-arm (53% vs 27%; P<.001) and phase I or II design (61% vs 31%; P<.001). Breakthrough indications offered a greater OS (HR, 0.69 vs 0.74; P=.031) and tumor response (RR, 1.48 vs 1.32; P=.006; ORR, 52% vs 40%; P=.004), but not a PFS benefit (HR, 0.53 vs 0.58; P=.212). Median improvements in OS (4.8 vs 3.2 months; P=.002) and PFS (5.4 vs 3.3 months; P=.005) but not duration of response (8.7 vs 4.7 months; P=.245) were higher for breakthrough than for nonbreakthrough indications. The BTD was more frequently granted to first-in-class drugs (42% vs 28%; P=.001) and first-in-indication treatments (43% vs 29%; P<.001). There were no differences in treatment and epidemiologic characteristics between breakthrough and nonbreakthrough drugs. Breakthrough drugs were more expensive than nonbreakthrough drugs (mean monthly price, $38,971 vs $22,591; P=.0592). Conclusions: The BTD expedites patient access to effective and innovative, but also expensive, new cancer drugs and indications.